The international discourse on the right to development and the need to reinvigorate its implementation - Yuefen Li; Daniel Uribe Terán; Danish (South Centre, 2022)
The world is currently at an ebb for realizing the Right to Development (RtD). Weakening of multilateralism, de-globalization, the scars left by the COVID-19 pandemic, misinterpretation and dilution of the RtD, and inertia to reform international governance are among the multitude of reasons for this phenomenon. However, the need for a better, more inclusive and greener recovery, and the efforts necessary to attain the 2030 Agenda, have provided the international community an opportunity to reinvigorate the realization of the RtD. These efforts have shown the great relevance of RtD to promote a people-centred and fairer development process and the need for an international enabling environment in order to promote the kind of development we want. This paper reviews the history of international discourse on RtD including major milestones, main divisive issues between the global South and the North, the evolution of voting patterns on intergovernmental outcomes, existing legal and political issues currently being discussed, the various mechanisms on the RtD, and recommendations on the way forward to revitalize the implementation of RtD at the 35th anniversary of the Declaration on Right to Development.
Keywords: 300; Entwicklung; Menschenrechte; Entwicklungshilfe; Entwicklungsländer